The association between nurses' moral distress and sleep quality and their influencing factor in private and public hospitals in Iran - Zeynab Rezaei Fard; Arman Azadi; Yousef Veisani; Amirreza Jamshidbeigi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Nurses in their workplace, for a variety of reasons, always face moral distress that is an underlying issue in the nursing profession, which can lead to problems such as reduced quality and quantity of care and sleep disorder. Besides, given the increased privatization of hospitals, this study aimed to explore the association between nurses' moral distress and sleep quality and its comparison among nurses in private and public hospitals. MATERIALS AND METHODS: This was a descriptive-analytical study involving 150 nurses working in Ilam Province hospitals. Sampling conducted using a multistage random sampling method. Data were collected through the questionnaire of sociodemographic characteristics, the Corley's Moral Distress Scale, and the Pittsburgh Sleep Quality Index. Data were analyzed using SPSS software version 22. Descriptive statistics such as frequency, mean, ANOVA, independent t-test, multiple linear regression, and Pearson correlation coefficient at the significant level of P < 0.05 were calculated. RESULTS: The analysis revealed that moral distress was positively associated with sleep quality. Furthermore, the scores of nurses' moral distress and sleep quality were different in private and public hospitals, so that the level of moral distress in the public hospital and sleep quality in the private hospital was higher and lower, respectively, but the difference was not statistically significant. Moreover, sleep quality, and the type of employment was the most important predicting variables of moral stress (B = 1.86) and sleep quality (B = 2.39), respectively. CONCLUSION: According to the study results, a positive and significant association was found between moral distress and nurses' sleep quality. It is recommended that appropriate strategies and training program be formulated by the health-care system to increase nurses' ability to combat moral distress adverse effects.